سلوك النمط (أ) واستراتيجيات المواجهة لدى معلمي المرحلة الابتدائية - فقيري,تونس (University of Eloued جامعة الوادي, 2024)
Abstract: The present study aimed to detect behavior type (A) , and coping strategies among primary school teachers in the city of El-Oued as a model. The sample of the study and composed of base was composed of (65) teachers chosen at random among primary school teachers in El-Oued. it was based on data collection tools which consisted in behavior scale type (A) in Muammria Bachir (2012). and scale of coping strategies by Esmahanne Asouz (2015). The study concluded the following results: - The primary school teacher has a behavior type A. - The primary school teacher has coping strategie . ملخص: هدفت الدراسة الحالية إلى الكشف عن سلوك النمط (أ) و استراتجيات المواجهة عند معلم المرحلة الابتدائية بمدينة الوادي نموذجا. وتكونت عينة الدراسة الأساسية من (65) معلما ومعلمة، اختيرت بطريقة عشوائية، من معلمي المدارس الابتدائية بمدينة الوادي ، كما تم الاعتماد في جمع البيانات على الأدوات التي تمثلت، في مقياس سلوك النمط (أ) لبشير معمرية (2012) و مقياس استراتجيات المواجهة لإسمهان عزوز (2015). خلصت الدراسة إلى النتائج التالية: - أن معلم المرحلة الابتدائية لديه سلوك النمط (أ). - أن معلم المرحلة الابتدائية لديه استراتجيات المواجهة.
دراسة ميدانية بمدينة الوادي
Keywords: سلوك النمط (أ); استراتجيات المواجهة; type (A) behavior; coping strategies; primary school teache